Cell death biomarkers as early predictors for hepatic dysfunction in patients after orthotopic liver transplantation - Brenner, Thorsten; Rosenhagen, Claudia; Brandt, Holger; Schmitt, Felix; Jung, Gregor Eric; Schemmer, Peter; Schmidt, Jan; Mieth, Markus; Bruckner, Thomas; Martin, Eike; Hofer, Stefan (Transplantation, 2012)
Background: Valid prognostic factors for early identification of a complicated course after orthotopic liver transplantation from deceased donors are rare. The aim of this study was to investigate the prognostic value of different cell death biomarkers and inflammatory markers in patients after orthotopic liver transplantation from deceased donors. Methods :In total, 100 patients were evaluated for short-term complications within 10 days after orthotopic liver transplantation from deceased donors. Blood samples were collected before surgery, immediately after the end of the surgical procedure, and 1 day and 3, 5, and 7 days later. Plasma levels of total keratin 18, keratin 18 fragments, interleukin 6, tumor necrosis factor α, and soluble intercellular adhesion molecule 1 were measured. Results: Total keratin 18 was demonstrated to be favorable in its prognostic value for early identification of a complicated course in comparison to routine markers of liver impairment (e.g., aspartate aminotransferase, alanine aminotransferase, lactate dehydrogenase). In contrast, inflammation markers (e.g., interleukin 6, tumor necrosis factor α and soluble intercellular adhesion molecule 1) were unsuitable for predicting early complications after liver transplantation from deceased donors. Conclusions: For early identification of patients at high risk for complications, the implementation of total keratin 18 measurements in routine diagnostics after orthotopic liver transplantation from deceased donors should be taken into consideration.